The demon of unrest ebook A saga of hubris, heartbreak, and heroism at the dawn of the civil war. - Larson, Erik (2024)
#1 NEW YORK TIMES BESTSELLER • The author of The Splendid and the Vile brings to life the pivotal five months between the election of Abraham Lincoln and the start of the Civil War in this “riveting reexamination of a nation in tumult” ( Los Angeles Times ). “A feast of historical insight and narrative verve . . . This is Erik Larson at his best, enlivening even a thrice-told tale into an irresistible thriller.”— The Wall Street Journal A PARADE BEST BOOK OF THE YEAR On November 6, 1860, Abraham Lincoln became the fluky victor in a tight race for president. The country was bitterly at odds; Southern extremists were moving ever closer to destroying the Union, with one state after another seceding and Lincoln powerless to stop them. Slavery fueled the conflict, but somehow the passions of North and South came to focus on a lonely federal fortress in Charleston Harbor: Fort Sumter. Master storyteller Erik Larson offers a gripping account of the chaotic months between Lincoln’s election and the Confederacy’s shelling of Sumter—a period marked by tragic errors and miscommunications, enflamed egos and craven ambitions, personal tragedies and betrayals. Lincoln himself wrote that the trials of these five months were “so great that, could I have anticipated them, I would not have believed it possible to survive them.” At the heart of this suspense-filled narrative are Major Robert Anderson, Sumter’s commander and a former slave owner sympathetic to the South but loyal to the Union; Edmund Ruffin, a vain and bloodthirsty radical who stirs secessionist ardor at every opportunity; and Mary Boykin Chesnut, wife of a prominent planter, conflicted over both marriage and slavery and seeing parallels between them. In the middle of it all is the overwhelmed Lincoln, battling with his duplicitous secretary of state, William Seward, as he tries desperately to avert a war that he fears is inevitable—one that will eventually kill 750,000 Americans. Drawing on diaries, secret communiques, slave ledgers, and plantation records, Larson gives us a political horror story that captures the forces that led America to the brink—a dark reminder that we often don’t see a cataclysm coming until it’s too late.